Dongo Sa'o Dongo Sa'o : The Matrilineal Marriage System Of The Ngada-Flores Community - Fatma Wati; Nong Hoban (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Abstract : Researchers have long been interested in studying the culture of the matrilineal marriage system, such as that of the Ngada tribe in the Flores archipelago, NTT. This matrilineal marriage system or Dongo Sa'o places women in a central position as guardians of the inheritance and women are the ones who have the right to decide the management of the inheritance. The husband is considered a good guest in the Sa'o or traditional house inherited from the wife's family and the children born in this marriage will follow the lineage of the mother. This is considered as a custom that has been determined by custom. This article discusses the uniqueness of the matrilineal marriage system that occurs in the Mangulewa village community, West Golewa District, Ngada Regency and the dynamics that arise because of these customary rules. Through an ethnographic approach, interviews and literature studies, it is known that the matrilineal marriage system in the Mangulewa village community is considered as for women because the rights and obligations attached to you guarantee the safety of their lives under any conditions. In the system of social strata that prevails in Ngada society in general, women in the matrilineal marriage system are still regarded as glorified figures. This can be seen from a series of stages of marriage, where at the approach stage will be started by the mother of the prospective groom and at the stage of proposing is also carried out by envoys consisting of women and the rights and obligations of husband and wife in this marriage bond. All stages of marriage must be inaugurated by custom or Zeza and affixed in the liturgical eucharistic ceremony at the Mater Dolorosa Mangulewa Parish Catholic Church. Keywords: Matrilineal Marriage System, Mangulewa